ANALYSIS OF THE WORK CARRIED OUT IN THE FIELD OF SPORTS AND MASS HEALTH IN THE REPUBLIC OF UZBEKISTAN - Sultonov Usmon Ibragimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Mass wellness sports activities are considered the main activities in the structure of the content of Physical Culture and do not set the task of developing the qualities of the movement of the organism engaged in the course of training.